P-Glycoprotein Expression on Patients with Acute Lymphoblastic Leukemia - R. Niiruri; I. Narayani; K. Ariawati; S. Herawati (Journal of Health Sciences and Medicine, 2017)
Abstract Objective: P-glycoprotein (P-gp) overexpression on neoplastic cells can deteriorate the therapeutic outcome on cancer patients. P-gp plays important role on drug efficacy and toxicity. This research aimed to measure P-gp expression on children with Acute Lymphoblastic Leukemia (ALL) on Sanglah Hospital, Denpasar. Method: Flowcytometry method was used to measure P-gp expression level on Bone Marrow samples from pediatric patients (0-12 years old) who were newly diagnosed with ALL in Sanglah Hospital. P-gp overexpression were based on the percentage of cell stained. Ten percent of P-gp expression were considered as the cut-off value of P-gp overexpression. Result: On this study, 11 samples were obtained with the range value of 56-97% on P-gp expression. Conclusion: All 11 patients had P-gp overexpression.